Nutrient availability and nutrient uptake as influenced by the post emergence application of herbicide mixtures - Raj, Sheeja K; Syriac, Elizabeth K (Journal of Tropical Agriculture, 2018)
Field experiments were conducted to study the effect of herbicide mixtures viz., bispyribac sodium + metamifop and penoxsulam + cyhalofop butyl on nutrient availability in soil, nutrient uptake by crop, nutrient removal by weeds and grain yield of direct seeded rice at Upanniyoor Padashekaram, Nemom block, Thiruvananthapuram, Kerala. Eleven weed control treatments along with weedy check were laid out in randomized block design with three replications. Results revealed that the lowest weed density, weed dry weight and nutrient uptake by weeds were observed in penoxsulam + cyhalofop butyl @ 135 g ha-1. Compared to weedy check, herbicide treatments reduced the N removal by weeds to the tune of 89.04 to 99.22 per cent and 89.67 to 99.36 per cent respectively at 60 DAS during Kharif 2014 and Rabi 2014-15 seasons. Phosphorus removal by weeds has been reduced to the tune of 70.59 to 98.04 per cent and K removal has been reduced to the tune of 86.22 to 99.42 per cent respectively at 60 DAS during Kharif and Rabi seasons. Among the different doses of bispyribac sodium + metamifop, its higher dose (90 g ha-1) was more effective in reducing the weed density and dry weight and nutrient depletion by weeds. Due to significant reduction in weed density and weed dry weight, penoxsulam + cyhalofop butyl @ 135, 130 and 125 g ha-1, bispyribac sodium + metamifop @ 90, 80 and 70 g ha-1 and penoxsulam applied alone recorded higher availability of N, P and K in soil and uptake of these nutrients by the rice crop. The weed management practices enhanced the grain yield from 4285 to 8295 kg ha-1 during first crop season and from 4240 to 8889 kg ha-1 during second crop season with 48.34 and 52.30 per cent increase in yield respectively over weedy check. During Kharif 2014, penoxsulam + cyhalofop butyl at 130 g ha-1 recorded the highest grain yield which was statistically on par with penoxsulam + cyhalofop butyl at 135 g ha-1 and 125 g ha-1. However, during Rabi 2014-15, penoxsulam + cyhalofop butyl at 135 g ha-1 recorded the highest grain yield which was significantly superior to all other treatments. Hence, post emergence application of penoxsulam + cyhalofop butyl @ 135 and 130 g ha-1 on 15 DAS can be recommended for the better control of weeds, nutrient availability and nutrient uptake by the crop and higher grain yield in wet direct seeded rice.